Animal models of metabolic syndrome: a review. Issue 1 (December 2016) - Wong, Sok; Chin, Kok-Yong; Suhaimi, Farihah Hj; Fairus, Ahmad; Ima-Nirwana, Soelaiman
Abstract Metabolic syndrome (MetS) consists of several medical conditions that collectively predict the risk for cardiovascular disease better than the sum of individual conditions. The risk of developing MetS in human depends on synergy of both genetic and environmental factors. Being a multifactorial condition with alarming rate of prevalence nowadays, establishment of appropriate experimental animal models mimicking the disease state in humans is crucial in order to solve the difficulties in evaluating the pathophysiology of MetS in human. This review aims to summarize the underlying mechanisms involved in the pathophysiology of dietary, genetic, and pharmacological models of MetS. Furthermore, we will discuss the usefulness, suitability, pros and cons of these animal models. Even though numerous animal models of MetS have been established, further investigations on the invention of new animal model and clarification of plausible mechanisms are still necessary to confer a better understanding to researchers on the selection of animal models for their studies.